Racial and Ethnic Representation and Study Engagement in a Siteless Digital Clinical Trial Using a Smartwatch: Findings From the Apple Heart Study - Kaylin T. Nguyen, MD; Jingzhi Yu, BA; Haley Hedlin, PhD; Adam T. Phillips, MD; Sumbul Desai, MD; Lauren Cheung, MD; Peter R. Kowey, MD; Sneha S. Jain, MD; John S. Rumsfeld, MD, PhD; Andrea M. Russo, MD; Christopher B. Granger, MD; Mellanie True Hills, BS; et al. (Mayo Clinic Proceedings: Digital Health, 2025)
Objective: To evaluate differences in study engagement in diverse racial/ethnic groups that have been significantly underrepresented in atrial fibrillation and digital clinical trials. Patients and Methods: This was a secondary analysis of participants from the Apple Heart Study, a prospective, siteless, single-arm pragmatic clinical trial from November 29, 2017, to January 31, 2019. Black, Hispanic, Asian, and White participants were monitored using an irregular rhythm notification algorithm designed to detect atrial fibrillation on a smartwatch. Logistic regression was performed to evaluate the relationship between race/ethnicity and completion of the first study visit after an irregular rhythm notification, adjusting for demographic characteristics and comorbidities. Results: Of the 419,297 participants, 393,396 (93.8%) individuals self-identified as White, Black, Hispanic, or Asian. Overall, participants were 57% men and had a mean (SD) age of 41 (13) years. Among 2044 (0.52%) participants who received an irregular rhythm notification, non-White participants had lower odds of completing the initial virtual study visit compared with White participants (Black: OR, 0.61; 95% CI, 0.39-0.94; Hispanic: OR, 0.62; 95% CI, 0.40-0.95; Asian: OR, 0.40; 95% CI, 0.23-0.66) after multivariate adjustment. Among those who completed the initial study visit, there was no statistically significant difference in the odds of returning the electrocardiogram patch in the non-White groups compared with that of the White group. Conclusion: Despite successful recruitment of racially and ethnically diverse participants, there were differences in subsequent engagement by non-White compared with that by White participants. Equitable representation and engagement of diverse racial and ethnic groups in digital clinical studies requires further study. Trial Registration: Clinicaltrials.gov Identifier: NCT03335800